2014
DOI: 10.1186/1756-0500-7-389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intubation and mechanical ventilation on exhaled nitric oxide in preterm infants with and without bronchopulmonary dysplasia measured at a median postmenstrual age of 49 weeks

Abstract: BackgroundExhaled nitric oxide (eNO) is a marker of established airway inflammation in adults and children, but conflicting results have been reported in preterm infants when postnatal eNO is measured during tidal breathing. This study investigated the extent to which intubation and mechanical ventilation (MV) affect eNO and NO production (V’NO) in preterm infants with and without bronchopulmonary dysplasia (BPD).Patients and methodsA total of 176 very low birth weight (VLBW) infants (birth weight <1500 g), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
10
0
2
Order By: Relevance
“…The children in the former study had higher levels of 8-isoprostane, a marker of oxidative stress, leading to speculation that noneosinophilic inflammation, such as neutrophilic inflammation, may be present in formerly premature children and lead to lower FeNO levels in children with asthma and history of BPD. Schmalisch et al have shown that former very-low-birth-weight infants undergoing infant lung function testing at an average of 49 weeks postmenstrual age have significantly lower FeNO if they had a history of receiving mechanical ventilation for <7 days compared to not having this history or receiving noninvasive mechanical ventilation [48]. Together, these studies imply that there are changes that may occur in the airway in formerly premature infants with and without history of BPD that may lead to a lower than expected FeNO value.…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…The children in the former study had higher levels of 8-isoprostane, a marker of oxidative stress, leading to speculation that noneosinophilic inflammation, such as neutrophilic inflammation, may be present in formerly premature children and lead to lower FeNO levels in children with asthma and history of BPD. Schmalisch et al have shown that former very-low-birth-weight infants undergoing infant lung function testing at an average of 49 weeks postmenstrual age have significantly lower FeNO if they had a history of receiving mechanical ventilation for <7 days compared to not having this history or receiving noninvasive mechanical ventilation [48]. Together, these studies imply that there are changes that may occur in the airway in formerly premature infants with and without history of BPD that may lead to a lower than expected FeNO value.…”
Section: Feno and Diagnosis Of Asthmamentioning
confidence: 99%
“…Schmalisch et al showed that FeNO levels were negatively correlated with tidal breathing parameters [48]. FeNO decreased with increased expiratory flow, indicating that measuring FeNO in sedated infants exhibiting tidal breathing may not be optimal to achieve a plateau in FeNO signal that is necessary to obtain an accurate value.…”
Section: Feno and Lung Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodological variability reported of eNO measurements has been pronounced. It includes off‐line or online measurements, adapted for research by counting and removing irregular breaths; hence, not applicable in a daily clinical setting. Measurements of eNO in premature mechanically ventilated neonates have been performed in the tube as well as in spontaneously breathing infants with a nasal prong or a facemask .…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al found decreasing eNO levels after 3 days of Dexamethasone in premature, chronically ventilated infants; possibly caused by de‐activation of the enhanced iNOS activity described in inflammatory processes . Inducible NOS is up‐regulated by oxidants, and proinflammatory cytokines Exhaled NO varies in children suffering from various lung diseases; supporting its use as a tool in the differential diagnostics …”
Section: Introductionmentioning
confidence: 99%